ANALISIS NERACA AIR PADA PERIODE KRITIS MUSIM TANAM PADI UNTUK MENILAI KEANDALAN SISTEM IRIGASI RAWA LEBAK (STUDI KASUS: DAERAH IRIGASI RAWA AMPUKUNG, KABUPATEN TABALONG) - Arifin Arifin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The swamp lowland irrigation system is strongly influenced by rainfall fluctuations and water level dynamics, which may cause an imbalance between water availability and irrigation water demand during the critical period of the rice-growing season. This study aims to analyze the water balance during the critical period in order to assess the reliability of the irrigation system in the Ampukung Swamp Irrigation Area, Tabalong Regency. Secondary data were obtained from the Detail Engineering Design (DED) document. The analysis was conducted on a semi-monthly basis by calculating 80% dependable discharge, evapotranspiration, and irrigation water requirements for rice at each growth stage. The results indicate that water deficits occurred during land preparation and early vegetative stages from January to February, with the maximum deficit reaching −8,075.56 L/s in early February and a minimum reliability ratio of 0.17. In contrast, surplus conditions were found during the late vegetative and generative stages, where the reliability ratio exceeded one. Critical-period water balance analysis provides a more specific assessment of water shortage risks compared to annual water balance evaluation. ABSTRAK Sistem irigasi rawa lebak dipengaruhi oleh fluktuasi curah hujan dan dinamika muka air sehingga berpotensi menimbulkan ketidakseimbangan antara ketersediaan dan kebutuhan air, terutama pada periode kritis musim tanam padi. Penelitian ini bertujuan menganalisis neraca air pada periode kritis untuk menilai keandalan sistem irigasi di Daerah Irigasi Rawa Ampukung, Kabupaten Tabalong. Data yang digunakan berupa data sekunder dari dokumen Detail Engineering Design (DED). Analisis dilakukan secara setengah bulanan dengan menghitung debit andalan 80%, evapotranspirasi, serta kebutuhan air irigasi tanaman padi pada setiap fase pertumbuhan. Hasil menunjukkan defisit air terjadi pada fase penyiapan lahan dan vegetatif awal selama Januari hingga Februari, dengan defisit maksimum sebesar −8.075,56 l/det pada Februari I dan rasio keandalan minimum 0,17. Sebaliknya, pada fase vegetatif lanjut dan generatif terjadi surplus air dengan rasio keandalan di atas satu. Analisis periode kritis memberikan gambaran risiko kekurangan air yang lebih spesifik dibanding neraca air tahunan.